Competitiveness of Indonesian Plantation Organic Coffee in the United States Market - Sania; Daspar (Samudra Publisher, 2025)
Indonesia is the world's fourth-largest coffee producer, known for its distinctive varieties such as Mandailing, Gayo, Kintamani, and Toraja. Amidst the growing global demand for organic products, especially in the United States market, Indonesian organic coffee holds significant potential to enhance its competitiveness. This study aims to analyze the opportunities and challenges of the competitiveness of Indonesian organic coffee in the U.S. market. A descriptive qualitative approach was employed using secondary data analysis derived from official reports, international trade statistics, and recent academic publications. The findings reveal notable opportunities, including U.S. consumers’ preference for organic, fair trade, and sustainable products. However, the sector faces substantial challenges, such as competition from other coffee-producing countries, non-tariff barriers like stringent organic certification requirements, producer fragmentation, and climate-related impacts. Strengthening Indonesia's position in the premium market requires a comprehensive strategy involving the enhancement of farmers’ institutional capacity, development of structured cultivation systems, and collaboration among key stakeholders.